Translating the Game: Ribosomes as Active Players - Calamita, Piera; Gatti, Guido; Miluzio, Annarita; Scagliola, Alessandra; Biffo, Stefano (Frontiers in Genetics, 2018)
Ribosomes have been long considered as executors of the translational program. The fact that ribosomes can control the translation of specific mRNAs or entire cellular programs is often neglected. Ribosomopathies, inherited diseases with mutations in ribosomal factors, show tissue specific defects and cancer predisposition. Studies of ribosomopathies have paved the way to the concept that ribosomes may control translation of specific mRNAs. Studies in Drosophila and mice support the existence of heterogeneous ribosomes that differentially translate mRNAs to coordinate cellular programs. Recent studies have now shown that ribosomal activity is not only a critical regulator of growth but also of metabolism. For instance, glycolysis and mitochondrial function have been found to be affected by ribosomal availability. Also, ATP levels drop in models of ribosomopathies. We discuss findings highlighting the relevance of ribosome heterogeneity in physiological and pathological conditions, as well as the possibility that in rate-limiting situations, ribosomes may favor some translational programs. We discuss the effects of ribosome heterogeneity on cellular metabolism, tumorigenesis and aging. We speculate a scenario in which ribosomes are not only executors of a metabolic program but act as modulators.